O contato entre português e pomerano em São Lourenço do Sul/RS: redes sociais e a produção de VOT - Damé, Vergília Spiering (2020)
The present work investigates the language contact between Portuguese and Pomeranian in bilingual´s speech in São Lourenço do Sul/RS, focusing on the production of VOT (Voice Onset Time) in the voiced and voiceless stops [p, t, k, b, d, g] in word-initial position. While in Portuguese these stops are differentiated through sonority, with prevoicing to characterize voiced stops and with short-lag, or even semi long-lag, to characterize the voiceless (KLEIN, 1999; ALVES, 2015), in Pomeranian they are differentiated through aspiration, being the voiced counterpart characterized by short-lag and the voiceless consonant by long-lag (SCHAEFFER; MEIRELES, 2011). In order to identify a possible transfer of VOT characteristics from Pomeranian to Portuguese, this work, in the light of a sociophonetic point of view, and based on the concept of social network (MILROY, 1987), investigates the speech of 40 participants, 30 Portuguese – Pomeranian bilingual speakers (sample PBB), 10 Portuguese monolingual speakers (sample PBM - Portuguese). The instrument to each data collection is divided in two speech styles: controlled and spontaneous. To the first, dissyllable words with stops followed by the vowels [a, e, i, o, u], in a stressed context in a CV syllable, were selected. To the Portuguese sample, the words were produced in vehicle sentences, Digo (target word) pra você, and to the Pomeranian sample, a translation of sentences was produced. The collection of spontaneous speech was made from interviews of personal experience. The participants, all female, were selected taking into account their age and living zone, either rural or urban. The speech data were recorded through Zoom H4N recorder. The acoustic analysis was conducted on PRAAT software, 6.0.28 version, and the statistical analysis was conducted on SPSS Statistics, version 20.0. The data analyzes reveals that the PBB sample presents an intermediate VOT duration between the PBM sample and the POM samples, but it differentiates meaningfully only in relation to the latter. Among the speech of the youngest bilinguals, the VOT duration is superior to the found in voiceless stops and inferior to the one in voiced stops, which vary between pre-voiced and short-lag tokens. The rural zone has shown to be a more favourable environment to the transfer of VOT characteristics from Pomeranian to Portuguese. The participants from the rural zone that are in dense and multiplex networks and in clusters show a significantly superior VOT duration, especially in voiceless stops. These results reveal the approximation of VOT duration between bilinguals from PBB sample and the monolinguals from the PBM sample, but advocate in favor of the social indexing hypothesis, since the participants in dense and multiplex social networks and in clusters reveal a similar VOT duration similar to Pomeranian.